The association between the frequency of physical activity and social background within and across home, occupational, transportation and leisure domains - Thomsen, Louise Briand; Schmidt, Eva Berthelsen; Dalgas, Birgitte Westerskov; Elmose-Østerlund, Karsten (Frontiers in Sports and Active Living, 2025)
This study investigates how often adults engage in physical activity across four life domains. Home, occupational, transport, and leisure using survey data from 163,000 Danes aged 15 and older. Activities were grouped into eleven categories, including housework, active transport, various types of training, sports, and outdoor activities. Descriptive statistics and multiple linear regression were used to examine patterns of participation and their association with social background, guided by ecological systems theory. Results show cumulative participation across activity types and significant variation linked to social background. The findings highlight the importance of distinguishing both between domains and between activity types within each domain when analyzing physical activity patterns.